Kajian tentang Doktrin Alkitab dari Perspektif Teologi Injili - Yornan Masinambouw (Pascasarjana IAKN Manado, 2020)
Based on the study and understanding that the Bible is the Word of God which is the basis of faith for every believer to be able to provide a transformative value of life to glorify Christ in church life, this article is intended to describe and formulate dogmatically the doctrine of the Bible from evangelical theology perspective. The research results obtained through the literature study approach that the Bible is the Word of God inspired by the Holy Spirit which also inspired the biblical writers to preach the News about the Kingdom of God for every believer. In addition, the Bible is also used as a benchmark for preaching the Word of God in the life of the church community. The implication for the reformatory church is that the church must return to the Bible as the reformers thought in accordance with the Sola Scriptura motto.